2009
DOI: 10.1155/2009/650340
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Patients with Multiple Recurrences of Well-Differentiated Thyroid Carcinoma

Abstract: Introduction. Patients with multiple recurrences of well-differentiated thyroid carcinoma (WDTC) have markedly reduced overall survival when compared with those who have ≤1 recurrence of their disease. The purpose of this investigation is to identify prognostic factors for mortality in this subgroup. Methods. Patients with multiple recurrences of WDTC were retrospectively identified from the thyroid cancer database at Mount Sinai Hospital, Toronto (1963–2000). Data on patient, tumor, and recurrence characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…As age increases, particularly after 48 years, the likelihood of unfavorable outcome increases. Similarly, young age was associated with favorable prognosis, consistent with a number of other studies (16,18,21). Previous studies demonstrated that patients with HTC or FTC were more likely to show unfavorable clinical outcomes compared with those suffering from PTC (22)(23)(24).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As age increases, particularly after 48 years, the likelihood of unfavorable outcome increases. Similarly, young age was associated with favorable prognosis, consistent with a number of other studies (16,18,21). Previous studies demonstrated that patients with HTC or FTC were more likely to show unfavorable clinical outcomes compared with those suffering from PTC (22)(23)(24).…”
Section: Discussionsupporting
confidence: 88%
“…Although WDTC is the most common type of thyroid carcinoma, it is the only type of this carcinoma with a low mortality rate (15)(16)(17) and increased survival rate; the current study found a rate of mortality of 4% for this condition. However, a number of studies have reported a mortality rate of ≤10% (5,18).…”
Section: Discussionmentioning
confidence: 43%
“…The MACIS score which was originally designed to stratify disease-specific survival may need a different cutoff to be predictive of incomplete response to therapy [16]. In one study, MACIS score cutoff of 6.0 was predictive for multiple recurrences and mortality among patients with DTC in a separate study involving all age groups [40,41]. There is also a trend showing higher TSH level among those with incomplete treatment response using comparison of means by t-test.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the type of initial treatment used, approximately 5% to 23% of patients present with cancer recurrence, which may be associated with a more virulent strain of the disease [10,11]. Although recurrences can be diagnosed decades later, most relapses occur within the first 5 years after treatment, and the first 18-24 months are considered the highest risk period for recurrence [12]. According to Palme et al, the male sex, advanced initial stage and the presence of extrathyroidal spread represent the most significant independent predictors of multiple recurrences in patients with WDTC.…”
Section: Discussionmentioning
confidence: 99%